1992
DOI: 10.1007/bf00178305
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of chromium-51 ethylene diamine tetra-acetic acid plasma clearance: a comparative assessment of simplified techniques

Abstract: Chromium-51 ethylene diamine tetra-acetic acid (51Cr-EDTA) total plasma clearance was evaluated using a multi-sample method (i.e. 12 blood samples) as the reference compared with several simplified methods which necessitated only one or few blood samples. The following 5 methods were evaluated: terminal slope-intercept method with 3 blood samples, simplified method of Bröchner-Mortensen and 3 single-sample methods (Constable, Christensen and Groth, Tauxe). Linear regression analysis was performed. Standard err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Picciotto et al [23] compared simplified one-sample methods with the two-compartment method and concluded that the Christensen and Groth [24] iterative method (using a single 5-hour sample) as the most accurate method. Gamma camera-based imaging methods for determination of GFR have been proposed by Piepsz et al [25] and Gates [26].…”
Section: Discussionmentioning
confidence: 99%
“…Picciotto et al [23] compared simplified one-sample methods with the two-compartment method and concluded that the Christensen and Groth [24] iterative method (using a single 5-hour sample) as the most accurate method. Gamma camera-based imaging methods for determination of GFR have been proposed by Piepsz et al [25] and Gates [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, nuclear medicine studies have replaced inulin clearance because of convenience and absence of urine collection. In Europe, 51 Cr-EDTA is the most widely used method for the determination of GFR (3), whereas in North America, the 99 Tc-diethylenetriamine pentaacetic acid renal scan enjoys the most widespread utilization (3)(4)(5). Although less demanding than inulin clearance studies, nuclear GFR studies are still cumbersome, invasive, and involve radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Although ECV is rarely used, it has been shown to be superior to BSA, especially in pediatric patients (32,33) where BSA is in meters squared, height is in centimeters, and weight is in kilograms. For 1-compartment characterization, it is important to perform BSA normalization before applying the quadratic Bröchner-Mortensen correction for the missing earlycompartment correction (10). The Bröchner-Mortensen correction is known to have the effect of overestimating GFR for patients with a GFR of above 80 mL/min/1.73 m 2 , particularly for patients with a BSA below 1 m 2 , such as in children.…”
Section: Gfr Normalizationmentioning
confidence: 99%